Soybean Oil Enriched with Antioxidants Extracted from Watermelon (Citrullus colocynthis) Skin Sap and Coated in Hydrogel Beads via Ionotropic Gelation - Muhammad Farooq (MDPI AG, 2021)
Many plants and fruits are rich in antioxidant and antimicrobial compounds, such as phenolic compounds. Watermelon is one example, as various parts of the fruit present interesting phytochemical profiles. This study demonstrates that a natural C. colocynthis (watermelon) (W) skin sap (SS) extract can effectively improve the oxidative stability of microencapsulated soybean (SB) oil. By employing a combination of alginate–xanthan gums (AXG) in a matrix hydrogel bead model with WSS extract, high encapsulation efficiency can be obtained (86%). The effects of process variables on the ultrasound-assisted extraction (UAE) of phenolic compounds from watermelon (W) skin sap (SS) using the response surface methodology (RSM), as an optimized and efficient extraction process, are compared with the effects of a conventional extraction method, namely the percolation method. The WSS extracts are obtained via UAE and RSM or the conventional percolation extraction method. The two obtained extracts and synthetic antioxidant butylated hydroxytolune (BHT) are added to SB oil separately and their antioxidant effects are tested and compared. The results show the improved oxidative stability of SB oil containing the extract obtained via the optimized method (20–30%) compared to the SB oil samples containing extract obtained via the percolation extraction method, synthetic antioxidant (BHT), and SB oil only as the control (no antioxidant added). According to existing studies, we assume that the use of WSS as an effective antioxidant will ensure the prolonged stability of encapsulated SB oil in hydrogel beads, as it is well known that extended storage under different conditions may lead to severe lipid oxidation.